Trends and level of development: View to new eu members - Gineviciene, Vanda; Tvaronaviciene, Manuela (Journal of Business Economics and Management, 2004)
The paper deals with evaluation of development level of new European Union members and 3 acceding counties. Authors elaborate existing systems of indicators and modern ranking methods used for indicated purpose. Presented analysis argues for superiority of statistical methods over qualitative ones in process of qualified evaluation of development level achieved by particular countries. New system comprising 12 indicators has been presented. The chosen set of indicators have emphasized three the most important dimensions, which provide stability of countries: economical, social and environmental. Evaluation of development tendencies during the last years of new the EU members and ascending countries has been done. Closer look at development level achieved by chosen countries comparing to that of EU‐15 has been taken. First published online: 14 Oct 2010